Pengaruh Brand Ambassador BTS terhadap Minat Beli Konsumen pada Marketplace Tokopedia - Suradi Suradi; Sri Sutalibani; Muthmainnah Mutmainnah; Kusno Utomo (Journal on Education, 2022)
This study aims to determine how much influence brand ambassadors have on consumer buying interest. This research design uses survey research that is quantitative in nature by taking a sample from one population, then using a questionnaire as a data collection tool. The population in this study is the community in the Jatiasih sub-district, Bekasi with a total sample of 80 respondents. Data collection techniques in this study are literature studies and questionnaires. The data analysis technique in this study is Simple Regression Analysis. The results of this study indicate that brand ambassadors have a positive effect on consumer buying interest. From the questionnaire data obtained from the respondents, the researcher conducted a simple regression test with the results obtained a constant (a) value of 32.458, while the brand ambassador value (b/regression coefficient) was 0.394. From these results, the regression equation can be entered as follows: Y= 32.458 + 0.394X. The results of the above equation can be translated as a constant of 32.458 which means that the consistency value of the brand ambassador variable is 32.458, the regression coefficient X is 0.394, which states that the addition of 1% of the brand ambassador value will increase buying interest by 0.394. The regression coefficient is positive, so it can be said that the influence of brand ambassador (X) on buying interest (Y) is positive. And based on the significance value obtained from the table above of 0.000 <0.05 so it can be concluded that the brand ambassador variable (X) has an effect on the buying interest variable (Y). The results of the coefficient of determination obtained coefficient of determination that is equal to 0.405 or 40.5%. The conclusion is that as much as 40.5% of the brand ambassador variables affect buying interest, while the remaining 59.5% is influenced by other variables outside the study